Closing the golden door : Asian migration and the hidden history of exclusion at Ellis Island - Pegler-Gordon, Anna, 1968- (University of North Carolina Press, 2021)
"The immigration station at New York's Ellis Island opened in 1892 and remained the largest U.S. port for immigrant entry until World War I. In popular memory, Ellis Island is typically seen as a gateway for Europeans seeking to join the 'great American melting pot.' But as this fresh examination of Ellis Island's history reveals, it was also a major site of immigrant detention and exclusion, especially for Chinese, Japanese, and other Asian travelers and maritime laborers who reached New York City from Europe, the Americas and the Caribbean, and even within the United States. And from 1924 to 1954, the station functioned as a detention camp and deportation center for a range of people deemed undesirable. Anna Pegler-Gordon draws on immigrants' oral histories and memoirs, government archives, newspapers, and other sources to reorient the history of migration and exclusion in the United States"--